PI3K-AKT signaling pathway is involved in hypoxia/thermal-induced immunosuppression of small abalone Haliotis diversicolor. (December 2016) - Sun, Yulong; Zhang, Xin; Wang, Guodong; Lin, Shi; Zeng, Xinyang; Wang, Yilei; Zhang, Ziping
Abstract: The PI3K-AKT signal pathway has been found to be involved in many important physiological and pathological processes of the innate immune system of vertebrates and invertebrates. In this study, the AKT ( HdAKT ) and PI3K ( HdPI3K ) gene of small abalone Haliotis diversicolor were cloned and characterized for the important status of PI3K and AKT protein in PI3K-AKT signaling pathway. The full length cDNAs of HdAKT and HdPI3K are 2126 bp and 6052 bp respectively, encoding proteins of 479 amino acids and 1097 amino acids, respectively. The mRNA expression level of fourteen genes in the PI3K-AKT signaling pathway were detected by quantitative real-time PCR. The results showed that all these fourteen genes were ubiquitously expressed in seven selected tissues. Meanwhile, HdAKT was expressed in haemocytes with the highest expression level (p < 0.05) next in hepatopancreas (p < 0.05). On the other hand, the expression level of HdPI3K in haemocytes was higher than other tissues. Under normal condition, the gene expression level of HdAKT, HdPI3K, and other PI3K-AKT signaling pathway members were significantly up-regulated by Vibrio parahaemolyticus infection which demonstrated that HdAKT, HdPI3K, and other PI3K-AKT signaling pathway members play a role in the innate immune system of abalone. The mRNA expression of these genes in gills, haemocytes and hepatopancreas was significantly down-regulated after the Vibrio parahaemolyticus stimulation with environment stimulation (thermal, hypoxia and thermal & hypoxia). These results indicate that the dual/multiple stresses defeat the immune system and lead to immunosuppression in abalone. PI3K-AKT signaling pathway may be involved in hypoxia/thermal-induced immunosuppression of small abalone Haliotis diversicolor. Highlights: The full-length cDNAs of PI3K and AKT from small abalone were cloned. Fourteen genes of PI3K-AKT signaling pathway were ubiquitously expressed in tissues. Gene expression of PI3K-AKT pathway was up-regulated after bacterial infection. Gene expression of PI3K-AKT pathway was down-regulated after bacterial under stress. PI3K-AKT pathway may be involved in hypoxia/thermal-induced immunosuppression in small abalone.